Localising a Spreadsheet: An Iban Example - Yeo, Alvin; Barbour, Robert (Malaysian Journal of Computer Science, 1997)
Presents an example of the localisation of a spreadsheet from English to Iban. The process by which the localisation has been carried out can be used as a framework for the localisation of software to languages of small ethnic minorities. Some problems faced during the localisation process are also discussed.